Meanings attributed by hospital psychologists to the relations between health professionals in the communication of bad news (Research, Society and Development, 2022)
This study aimed to understand meanings attributed by hospital psychologists to the relations between health professionals from different areas in situations of bad news communication. This is a qualitative study, whose participants were 17 hospital psychologists who worked in Brazilian public general hospitals. The number of participants was determined through saturation criterion. Data collection was carried out by conducting a semi-directed and audio-recorded interview with each participant. Transcripts of recordings were submitted to content analysis. It was found that the meanings attributed to the participants to the relations that health professionals from different areas establish among themselves in situations of bad news communication were anchored in a temporal parameter, around which were demarcated specific responsibilities that encourage distancing and make approximations difficult, especially between physicians and hospital psychologists. Furthermore, some participants valued collaborative work, but not its materialization through the practical integration of specialized knowledge. This study allows the circumscription of obstacles to interdependence that can only be overcome if all health professionals face the psychological suffering triggered in situations of bad news communication as a subjective urgency.